Hubungan Pengetahuan dan Sikap Personal Higiene Remaja Putri Saat Menstruasi dengan Kejadian Infeksi Saluran Repoduksi Kecamatan Seram Barat - Herlin Sinay; Ety Dusra; Desy Vralenda Manuputty (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
The prevalence of Reproductive Tract Infections (RTIs) in Indonesia remains quite high. This is primarily due to the poor personal hygiene practices of most adolescents. Objective: This study aims to determine the relationship between knowledge and attitudes with personal hygiene behavior during menstruation among adolescent girls in Manipa Hamlet, Piru Village, West Seram District. Methodology: This research employs a quantitative approach with a cross-sectional study design. The sampling technique used is total sampling. Data were collected using a questionnaire measuring knowledge, attitudes, and personal hygiene behavior during menstruation. Data analysis was conducted using univariate and bivariate analysis and statistical analysis using the chi-square test, with a significance level (p-value).